An international review of occupant-related aspects of building energy codes and standards. (15th July 2020) - O'Brien, William; Tahmasebi, Farhang; Andersen, Rune Korsholm; Azar, Elie; Barthelmes, Verena; Belafi, Zsofia Deme; Berger, Christiane; Chen, Dong; De Simone, Marilena; Simona d'Oca; Hong, Tianzhen; Jin, Quan; et al.
Abstract: In light of recent research, it is evident that occupants are playing an increasingly important role in building energy performance. Despite the important role of building energy codes and standards in design, the occupant-related aspects are typically simple and have not kept up with the leading research. This paper reviews 23 regions' building energy codes and standards by first comparing their quantitative aspects and then analyzing their mandated rules and approaches. While the present paper focuses on offices, general recommendations are applicable to other building types as well. The review revealed a wide range of occupant-related values, approaches, and attitudes. For example, code-specified occupant density varies by nearly a factor of three between different codes. This underlines the need for development of advancement in occupant behavior modeling approaches for future occupant-centric building performance codes and standards. Moreover, occupants are often referred to only implicitly; underlying expectations about energy-saving occupant behavior from building occupants varies greatly; and, only a few codes address occupant feedback and system usability. Based on the findings of the review, a set of initial recommendations for future building energy codes is proposed. Highlights: Codes are critical for energy efficiency, yet occupant aspects are simplistic. 23 regions' building energy codes/standards were reviewed for occupant aspects. Both performance and prescriptive paths were compared and contrasted. Schedules and densities between codes vary by as much as a factor of three. Mention of occupants in building energy codes is often only indirect and implicit.